2013
DOI: 10.1186/1476-4598-12-37
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes induced by the curcumin analogue D6 in human melanoma cells

Abstract: BackgroundIn a previous report, we described the in vitro and in vivo antiproliferative and proapoptotic activity of a hydroxylated biphenyl (D6), a structural analogue of curcumin, on malignant melanoma and neuroblastoma tumours. In this paper, we investigated the molecular changes induced by such a compound, underlying cell growth arrest and apoptosis in melanoma cells.ResultsTo shed light on the mechanisms of action of D6, we firstly demonstrated its quick cellular uptake and subsequent block of cell cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…It has been reported that the antiproliferative property of D6, a curcumin analogue, in melanoma could be partially due to the downregulation of the PI3K/AKT pathway (22). Proverbially PI3K/AKT/mTOR/P70S6K pathway is a critical intracellular signaling pathway with respect to cell survival and death (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the antiproliferative property of D6, a curcumin analogue, in melanoma could be partially due to the downregulation of the PI3K/AKT pathway (22). Proverbially PI3K/AKT/mTOR/P70S6K pathway is a critical intracellular signaling pathway with respect to cell survival and death (23).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that extreme concentrations of curcumin reduce cell viability [33]. This could activate the p53 signaling pathway and block the cell cycle in the G2/M phase (down-regulation of PI3K/Akt and NF-kB pathways) [34]. Therefore, these studies have illustrated that the activities of curminoids depend on the examined biological action and the cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this analysis pointed out the induction of strong cell stress responses, with up regulation of several heat shock proteins (HSPs) and involvement of protein ubiquitination and stress response pathways, including p53 driven pathways, strongly supporting the pro-apoptotic activity previously observed. Cell proliferation pathways were instead down-modulated [ 10 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%